Innocent of Moscow, the apostle of Kamchatka and Alaska [electronic resource] - Hale, Charles R. (Charles Reuben), 1837-1900 ([Davenport, Iowa? : s.n.], 1888)
"Privately printed." Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44